Direct visualization of hydrogen absorption dynamics in individual palladium nanoparticles - Tarun C. Narayan (Nature Portfolio, 2017)
It remains unclear why energy storage systems with nanoscale constituents are less susceptible to stress-induced damage than their bulk counterparts. Here, the authors probe in real time the intercalation-driven phase transitions of nanoscale palladium hydride, finding that these nanoparticles are able to fix crystallographic flaws as they form.